Cardiovascular reactivity to stress in long-term yoga practitioners - Arijita Banerjee; Sumit Kumar (Journal of Family Medicine and Primary Care)
Background: Bhramari Pranayama yogic breathing is a very simple exercise of voluntary breathing which mitigates stress reactivity through autonomic modulation of heart rate. Aim: To study the effects of long-term practice of the yoga breathing exercise on cardiovascular reactivity to head-up tilt (HUT) test. Methods: All the participants were subjected to a 10-item yoga questionnaire. Based on Likert scale scoring, 32 subjects (group I) were selected as long-term yogic breathing practitioners, and autonomic function tests using heart rate variability (HRV) and a provocative stress test and HUT test were conducted. Cardiovascular parameters obtained were compared with controls who had never been engaged in any form of yoga (group II). Results: A highly significant decrease in values of both high (HF) and low frequency (LF) variables was observed in group II as compared to group I. However, a highly significant rise in LF/HF has been observed in group I compared to group I (P = 0.004), further indicating a greater withdrawal of vagal tone during the HUT test and also during recovery (P = 0.001). Discussion: The results and discussion of HRV analysis during provocative tests concluded that autonomic imbalance was present in the subjects who were not exposed to any form of yoga. Thus, it is advisable to practice yoga in any form regularly to mitigate the early onset of autonomic dysfunction.